ANTIMICROBIAL ACTIVITY OF Actinomycetes EXTRACT FROM SEA WATER OF RANDAYAN ISLAND, AGAINTS Salmonella sp. - ., Rahmi Dianty (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2015)
Background: Typhoid fever is still problem in the world. Actinomyetes, microbe produces antibiotic. Discovery new antibiotic is a need to handle Multiple Drug Resistant Typhoid Fever. Isolation Actinomycetes which produces secondary metabolite can be made by exploring marine. Objective: to know the potentially of Actinomycetes isolate which was founded as antibiotic producer againt Salmonella sp. Method: Antimicrobial activity of 16IM7 isolate extract from Randayan Island, Bengkayang Disctrict is observated againt Salmonella sp. Dose variation is 5, 10, and 15 µg. Positive control is cefixime 10 µg/disk and negative control is etil asetat. Result: based on the research by well diffusion agar methode is known that 16IM7 isolate extract could inhibit Salmonella sp and optimum dose is 10µg. Minimum inhibit consentration (MIC) is 0,25 µg /well.Conclusion: Actinomycetes was isolated from marine potentially as antibiotic producer against Salmonella sp. Kata Kunci: typhoid fever, antimicrobial, Actinomycetes, Salmonella sp